2011
DOI: 10.1109/tps.2011.2141689
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Asperity-Scale Plasma Discharge Phenomena

Abstract: A combined experimental and computational simulation study of direct-current plasma discharge phenomena in small-length-scale geometries (< 10 µm) is described. The primary goal is to study discharge breakdown characteristics in small-length-scale geometries as quantified by a modified Paschen breakdown curve and the quench characteristics in these discharges. A modified mesoscale friction tester apparatus is used for the experiments. A self-consistent nonequilibrium plasma model is used for the simulation stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…This is due to the fact that the MCD thruster operates at pressures ∼40 kPa and discharge gaps ∼100 µm which corresponds to a pd (pressure×discharge gap) ∼3 Torr cm. Field emission is seen to play an important role in discharges with extremely small inter electrode distances typically at a pd ∼ 0.2 Torr cm [14]. Secondary electron emission due to electron impact is also neglected here.…”
Section: Plasma Governing Equationsmentioning
confidence: 99%
“…This is due to the fact that the MCD thruster operates at pressures ∼40 kPa and discharge gaps ∼100 µm which corresponds to a pd (pressure×discharge gap) ∼3 Torr cm. Field emission is seen to play an important role in discharges with extremely small inter electrode distances typically at a pd ∼ 0.2 Torr cm [14]. Secondary electron emission due to electron impact is also neglected here.…”
Section: Plasma Governing Equationsmentioning
confidence: 99%
“…2 below pd~2 Torr.cm. Recent experiments, however, have shown that the breakdown voltage decreases monotonously for small gaps [19][20][21][22][23][24] that are less than 10 μm in 1 Atmosphere in air. The cause of this behavior is attributed to ion-enhanced field emission that occurs as the positive ions approach the negative electrode (cathode).…”
Section: Fig 2: Paschen Curves For 5 Different Gases Of Importance Imentioning
confidence: 96%
“…As the gap distance is reduced below 10 μm at 1 atmosphere in nitrogen, the Paschen curve predicts very large breakdown voltages that is experimentally shown not to be accurate. The ion-assisted field emission takes over in this regime and lowers the breakdown voltage considerably [19][20][21][22][23][24]. If it wasn't for the ionassisted emission process, it would have been impossible to realize MPDs with single digit breakdown voltages.…”
Section: Introductionmentioning
confidence: 99%
“…As the gap distance is reduced below 10 μm at 1 atmosphere in nitrogen, the Paschen curve predicts very large breakdown voltages, which is experimentally shown not to be accurate. The ion-assisted field emission takes over in this regime and lowers the breakdown voltage considerably [ 19 , 20 , 21 , 22 , 23 , 24 ]. If it were not for the ion-assisted emission process, it would have been impossible to realize MPDs with single digit breakdown voltages.…”
Section: Introductionmentioning
confidence: 99%
“…Thus the breakdown voltage increases as indicated by the above equations and shown in Figure 2 below pd ≈ 2 Torr·cm. Recent experiments, however, have shown that the breakdown voltage decreases monotonously for small gaps [ 19 , 20 , 21 , 22 , 23 , 24 ] that are less than 10 μm in 1 Atmosphere in air. The cause of this behavior is attributed to ion-enhanced field emission that occurs as the positive ions approach the negative electrode (cathode).…”
Section: Introductionmentioning
confidence: 99%